Recruter l’intelligence collective pour niveler la stratification du monde de l’art : comment les musées virtuels d’art contemporain peuvent-ils avoir un impact sur le système artistique actuel ? - Bertrand, Stéphanie (Muséologies, 2026)
Shifting away from the cultural impacts of physical museums to the virtual realm, this article explores two important benefits of digitized online art collections. Based on empirical research, it aims to demonstrate that these increasingly interconnected collections have the potential to activate a new model of cultural participation capable of sustaining power-sharing that goes beyond public consultation, and of transforming the stratification inherent in the art system, by opening up access barriers to institutional prestige in the art world, to the benefit of artists, by levelling the playing field. The argument is that digitized art collections can serve as a digital infrastructure for recruiting collective intelligence on a mass scale to democratize culture and foster equality and diversity in the art world. However, these impacts cannot be achieved simply by transforming users into citizen curators, or by leveraging alternative impact metrics or “altmetrics” (i.e., views and likes) to influence selection and alter order within an aggregated or distributed database. The main obstacle to achieving these virtual impacts is neither limited online access, nor insufficient participation. Multiplying users, facilitating discovery and promoting public choices are all essential; but these initiatives cannot hope to transform the art system if the individual judgments captured are subject to various spheres of influence and to network effects productive of inequalities. To overcome these effects, the article proposes a new choice-based “pathfinding” tool, designed to recruit users’ sensemaking faculty as opposed to their personal tastes, and in so doing, more effectively capture what users find meaningful and establish a new value proposition for art.